Ethical guidance for geriatric clinical research in China. Issue 4 (21st December 2020) - Yu, Lingling; Li, Xiaoling; Zhang, Pengjun; Zhang, Guojun
Abstract: In China, the population is aging rapidly, and the elderly have enormous medical needs. However, the elderly are underrepresented in clinical research, potentially forcing them to use medical devices and treatments that may be not suitable for them. Elderly patients are characterized by multiple comorbidities, concomitant treatments, and high incidence of cognitive impairment, and consequently are at increased risk of participating in clinical research. To reduce the risks involved with the elderly participating in clinical research, guidance on the ethical review of geriatric research is necessary. Based on a literature review and panel discussion, we have developed the Ethical Guidance for Geriatric Clinical Research, aiming to provide guidance on the ethical review of geriatric clinical research.